Study of Oil Palm Frond (OPF) and Oil Palm Trunk (OPT) for Sustainable Development - Yacob N.S.; Mohamed H.; Shamsuddin A.H. (Springer Science and Business Media Deutschland GmbH, 2023)
Bioconversion; Fossil fuels; Greenhouse gases; Palm oil; Sustainable development; Environmental emissions; Frond; Greenhouses gas; Malaysia; Oil palm; Oil palm biomass; Oil palm frond; Oil palm trunks; Renewable energies; Trunk; Biomass